Islamic values contained in university students’ quatrains in the whatsapp group - Dewi Warna (Universitas Muhammadiyah Malang, 2020)
Quatrains used to live among Malays in Indonesia, especially in South Sumatera. But now, not many people in South Sumatera use quatrains in daily life interactions among people in society. It makes quatrains almost extinct. Fortunately, a group in whatsapp namely “Grup Pantun Mahasiswa” tries to remain using quatrains in communicating among the group members. The objective of this research is to find out the Islamic values contained in the quatrains made by the students of Faculty of Tarbiyah and Teaching Sciences, Indonesia, in the whatsapp group. The method of this research was descriptive qualitative. In collecting the research data, the researcher collected the quatrains in the whatsapp group since January 21, 2019 to July 21, 2019. These quatrains were made by 321 students of Faculty of Tarbiyah and Teaching Sciences as the members of the whatsapp group. The group’s name is “Grup Pantun Mahasiswa”. The number of the quatrains was 649 quatrains. Next, in analyzing the research data, first of all, the researcher read and presented the quatrains in the whatsapp group. Then she classified them into topic categories: Islamic and non-Islamic topic categories. The Islamic topic categorized quatrains were subcategorized into its Islamic values. The Islamic values were then described one by one. The result of the analysis showed that out of 649 quatrains, Islamic values contained in the quatrains made by the whatsapp group members are the followings: (1) worshipping God (praying, fasting, and giving alms); (2) the sunnah of marriage; (3) respecting parents; (4) appreciating elders; (5) diligence in working & fulfilling invitations; (6) supporting one another in achieving goals; (7) comforting the sad; (8) asking for forgiveness and forgiving one another; (9) the importance of silaturrahim; (10) suggestions of doing good deeds; (11) competing in doing good deeds; (12) forbidding doing the harms; (13) helping one another; (14) praying for one another’s success; (15) unity among Muslims; and (16) praising God’s creatures. In conclusion, out of 649 quatrains as the research data, 51 quartains contained Islamic values. While, other 598 quatrains did not contain any Islamic values.